EXPERIMENTAL INVESTIGATION OF DROPLET EVAPORATION AND MICRO EXPLOSION BEHAVIOUR OF GAS-TO-LIQUID (GTL) FUEL - ROSLI, MOHD ARIF FAHMI (2020)
Gas-to-Liquid (GTL) fuel is considered as clean fuel alternatives and has been given much attention as a replacement for conventional fuel. Unfortunately, there exist a minimal number of studies discussing the behaviour of the droplet evaporation and micro-explosion of GTL fuel blends.